2018
DOI: 10.1523/eneuro.0051-18.2018
|View full text |Cite
|
Sign up to set email alerts
|

A Brain without Brakes: Reduced Inhibition Is Associated with Enhanced but Dysregulated Plasticity in the Aged Rat Auditory Cortex

Abstract: During early developmental windows known as critical periods (CPs) of plasticity, passive alterations in the quality and quantity of sensory inputs are sufficient to induce profound and long-lasting distortions in cortical sensory representations. With CP closure, those representations are stabilized, a process requiring the maturation of inhibitory networks and the maintenance of sufficient GABAergic tone in the cortex. In humans and rodents, however, cortical inhibition progressively decreases with advancing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
35
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 83 publications
(125 reference statements)
4
35
0
Order By: Relevance
“…The present findings, obtained using temporally degraded modulated sounds in young-adult MGB units, support our hypothesis that modelled ageing using temporally degraded stimuli in young rats. These findings are consistent with studies showing an age-related increase in predictable preference or an increase in firing with repetition (de Villers-Sidani et al 2010;Cai et al 2016;Cisneros-Franco et al 2018). We postulated this to be the result of a temporally jittered/less salient code in aged MGB that frequently led to increases in firing with repetition.…”
Section: Effects Of Ageing On Central Auditory System and Top-down Prsupporting
confidence: 91%
See 2 more Smart Citations
“…The present findings, obtained using temporally degraded modulated sounds in young-adult MGB units, support our hypothesis that modelled ageing using temporally degraded stimuli in young rats. These findings are consistent with studies showing an age-related increase in predictable preference or an increase in firing with repetition (de Villers-Sidani et al 2010;Cai et al 2016;Cisneros-Franco et al 2018). We postulated this to be the result of a temporally jittered/less salient code in aged MGB that frequently led to increases in firing with repetition.…”
Section: Effects Of Ageing On Central Auditory System and Top-down Prsupporting
confidence: 91%
“…A second ageing MGB study by Cai et al (2016) used complex longer duration SAM stimuli stepped between 2 and 1024 f m and found significant age-related changes in the response properties of MGB neurons when a random presentation was compared with a predictable/repeating presentation of stimuli. These findings are consistent with studies performed in aged rat auditory cortex showing a decrease in SSA (de Villers-Sidani et al 2010;Cisneros-Franco et al 2018). The use of a relatively long SAM stimulus is more complex than the short pure tones used in most SSA studies and may more closely represent animal vocalizations and human speech.…”
Section: Effects Of Ageing and Top-down Processes In The Medial Genicsupporting
confidence: 91%
See 1 more Smart Citation
“…These results have been supported by recent animal studies which showed a deleterious effect of aging at the level of the brainstem but enhanced responses to temporally varying stimuli at the level of the primary auditory cortex (Occelli et al, 2019). Different central mechanisms have been proposed to contribute to these potentially paradoxical observations, including changes in central gain as compensation for degraded auditory input (Chambers, Resnik, et al, 2016;Chambers, Salazar, & Polley, 2016), changes in cortical connectivity (Peelle, Troiani, Wingfield, & Grossman, 2010), or altered excitatory and inhibitory balance within the aged cortex (Cisneros-Franco et al, 2018;Hughes, Turner, Parrish, & Caspary, 2010;Recanzone, 2018;Stebbings et al, 2016). However, the effect of age-related changes on the medial geniculate body (MGB, the principal region of the auditory thalamus), which is directly connected to both the IC and the auditory cortex (see Figure 1), has not been considered.…”
Section: Introductionmentioning
confidence: 62%
“…Such suggestions are supported by electrophysiological data, associating communication problems with temporal processing deficits within the auditory brainstem (Caspary, Hughes, Schatteman, & Turner, 2006;Caspary, Schatteman, & Hughes, 2005), midbrain (Parthasarathy & Bartlett, 2011;Presacco, Simon, & Anderson, 2016a, 2016bWalton, Frisina, & O'Neill, 1998), or cortex (Mendelson & Ricketts, 2001; Presacco et al, 2016aPresacco et al, , 2016b. These age-related deficits in auditory processing throughout the central auditory pathways have been variously linked to alterations in: inhibitory signaling (Caspary, Ling, Turner, & Hughes, 2008), GABAergic transmission (Burianova, Ouda, Profant, & Syka, 2009;Cisneros-Franco, Ouellet, Kamal, & Villers-Sidani, 2018;Pal et al, 2019), cholinergic dysfunction (Sottile et al, 2017), parvalbumin positive (PV+) neurons (Cisneros-Franco et al, 2018;Gray, Engle, Rudolph, & Recanzone, 2014;Pal et al, 2019); and glial cells (Tremblay, Zettel, Ison, Allen, & Majewska, 2012). However, many studies investigating aging use old animals or animal-models of accelerated aging to investigate age-related changes within the auditory system, for example CBA/ CaJ mice beyond 80 weeks of age, C57/Bl6 mice (Sergeyenko, Lall, Liberman, & Kujawa, 2013) or Fisher Brown Norway rats (Cai, Montgomery, Graves, Caspary, & Cox, 2018).…”
Section: Introductionmentioning
confidence: 90%